Overcoming immunotherapy resistance in glioblastoma: challenges and emerging strategies - Fu, Maowu; Xue, Bing; Miao, Xiuming; Gao, Zong (Frontiers in Pharmacology, 2025)
Glioblastoma (GBM) is the most common and aggressive primary brain tumor in adults, characterized by rapid proliferation, extensive infiltration, and significant intratumoral heterogeneity. Despite advancements in conventional treatments, including surgery, radiotherapy, and chemotherapy, the prognosis for GBM patients remains poor, with a median survival of approximately 15 months. Immunotherapy has emerged as a promising alternative; however, the unique biological and immunological features, including its immunosuppressive tumor microenvironment (TME) and low mutational burden, render it resistant to many immunotherapeutic strategies. This review explores the key challenges in GBM immunotherapy, focusing on immune evasion mechanisms, the blood-brain barrier (BBB), and the TME. Immune checkpoint inhibitors and CAR-T cells have shown promise in preclinical models but have limited clinical success due to antigen heterogeneity, immune cell exhaustion, and impaired trafficking across the BBB. Emerging strategies, including dual-targeting CAR-T cells, engineered immune cells secreting therapeutic molecules, and advanced delivery systems to overcome the BBB, show potential for enhancing treatment efficacy. Addressing these challenges is crucial for improving GBM immunotherapy outcomes.